Refactoring for Usability in Web Applications - Garrido, Alejandra (2011)
Refactoring was originally conceived as a technique for enhancing the design of an existing code base by applying small behavior-preserving transformations to the code. Later research extended scope of refactoring to other software artifacts, such as design models, and widened its intent to improve additional software quality factors, such as performance. In this article, the authors discuss how to improve the usability of a Web application by applying refactoring on its design structure. We also classify each refactoring by the specific usability factor it improves and the bad usability smells it targets. Some examples of Web model refactorings illustrate our claims.